Strategy for Implementing the Blue Economy Concept for Community Empowerment in Achieving Sustainable Development Goals - Masni, Harbeng; Hutabarat, Zuhri Saputra; Rahmadani, Cindy; Yulita, Kintan; Putri, Riska Ananda; Nurwati, Nurwati; Pianti, Uut Okta; Safitri, Rahmah; Ramadani, Novita; Deskiana, Intan; Alfarizi, Rizky Putri; Putri, Rima Melani; Yuliana, Eni (International Journal of Multidisciplinary Sciences and Arts, 2024)
Indonesia has around 17,500 islands spread throughout the archipelago and a coastline that stretches for 81,000 km, more than half of Indonesia's total area is sea and water. This geographical condition makes Indonesia a country that has rich marine resources. However, challenges such as illegal fishing and lack of empowerment of coastal communities threaten the sustainability of the fisheries sector. Implementing the Blue Economy concept is the key to achieving Sustainable Development Goals (SDGs). Through a literature study, this article investigates strategies for implementing the Blue Economy in empowering communities in Indonesia to achieve the SDGs, especially goal 14: Life Below Water. Strategic steps are needed such as increasing supervision, developing technology and building infrastructure to improve community welfare and maintain the sustainability of marine resources. With great potential in the aquaculture sector, Indonesia can realize the vision of sustainable development through collaboration between various parties and the application of innovative and sustainable Blue Economy principles.